Edukasi dan Sosialisasi Isi Piringku pada Siswa Madrasah Ibtidaiyah Al-Falah Kabupaten Gorontalo - Sabrina Nadjib Mohamad; Ingka Rizkyani Akolo; Dewi Darmiyani Napu; Suharia Sarif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The prevalence of nutritional status among children aged 5-12 in the Gorontalo Province based on BMI-for-age indicates that 2.70% are severely underweight, 8.45% are underweight, 8.93% are overweight, and 6.26% are obese. The shift from the previous 'four healthy five perfect' nutrition reference to balanced nutrition guidelines is not yet fully understood and known by all layers of society, including within school environments. The outreach activity conducted at Al-Falah Elementary Islamic School in Gorontalo District aims to provide education and socialization regarding balanced nutritional guidelines and the concept of 'My Plate' to elementary school students. The participants involved 34 students from grades 4 and 5. The methods employed included lectures, video presentations, followed by an evaluation using a 'My Plate' puzzle assembly game. The utilization of the puzzle as an evaluation medium was well comprehended by the students, as evidenced by a 75% proficiency in completing the puzzle. Enhancing students' knowledge about balanced nutritional guidance and food plate composition can be achieved through nutritional education and socialization.